The zinc-finger transcriptional factor Slug transcriptionally downregulates ERα by recruiting lysine-specific demethylase 1 in human breast cancer - Bai, J-W (Oncogenesis, 2017)
Estrogen receptor α (ERα) is related with epithelial–mesenchymal transition, invasion and metastasis, and serves as an important therapeutic predictor and prognostic factor in breast cancer patients. The triple negative breast cancer (TNBC) is characterized by loss of hormone receptors and human epidermal growth factor receptor 2 (Her2), and lacks effective targeted therapy with poor prognosis. Unfortunately, the molecular mechanisms of ERα deficiency, which becomes hormone independent and results in resistance to endocrine therapy, remain to be elucidated in breast cancer. In this study, we observed an inverse correlation between Slug, a zinc-finger transcriptional repressor, and ERα expression in both human breast cancer tissues and cell lines. In ERα-negative breast cancer patients, high Slug messenger RNA expression showed obviously shorter relapse-free survival. We found that Slug binds to the E-box located in the promoter of estrogen receptor 1 gene (ESR1) to suppress its expression. More specifically, Slug recruits lysine-specific demethylase 1 (LSD1) to the E-box and thereby inhibits ERα expression by demethylating H3K4me2, which is evidenced by the interaction between Slug and LSD1. Moreover, the amount of H3K4me2 binding to the E-box was significantly increased after LSD1 knockdown in MDA-MB-231 cells. Functionally, the ability to proliferate, invade and metastasize was significantly suppressed after knockdown of either Slug or LSD1 alone, or both simultaneously. Taken together, these results suggest that Slug transcriptionally inhibits ERα expression by recruiting LSD1 to the ESR1 promoter in breast cancers. Thus, targeted inhibition of Slug and LSD1 may restore ERα and lead to resensitization to hormone therapy, providing a novel therapeutic strategy for ERα-negative breast cancer patients, especially for TNBC.